The Risk of Arrhythmias in Patients with COVID-19 - Lina Haj Ali; Loredana Suhov; Adrian Apostol; Larissa Dăniluc; Oana Sandu; Carina Bogdan; Viviana Mihaela Ivan (Biomedicines, 2025)
Background and Objectives: Cardiac arrhythmias during the SARS-CoV-2 infection may occur due to the direct impact of the virus on the respiratory and cardiovascular systems, as well as through the broader effects of systemic inflammation, or a combination of both. Additional mechanisms include the proarrhythmic effects of COVID-19 pharmacotherapies, drug–drug interactions, and associated autonomic dysfunction. To improve future risk stratification and clinical management, it is essential to accurately assess the risk of arrhythmia in the context of severe infections, in order to develop diagnostic and therapeutic algorithms that support the fastest and safest possible interventions. Materials and Methods: This retrospective observational study included 151 patients diagnosed with COVID-19, who were hospitalized at the Cardiology Clinic of the Timisoara County Emergency Hospital between 2020 and 2022. Results: The most common arrhythmia observed was atrial fibrillation. Elevated inflammatory markers were associated with a higher risk of arrhythmias and increased mortality. Conclusions: The onset of sepsis, as indicated by the laboratory markers, was associated with increased incidence of arrhythmias and unfavorable outcome of the disease.